Deciphering phytomicrobiomes for sustainable crop production: Recent findings and future perspectives - Vikash Kumar; Nikhil Raghuvanshi; Abhishek Kumar; Lellapalli Rithesh; Alok Rai; Abhay K. Pandey (Plant Stress, 2023)
The study of plant-microbiome interactions is critical for developing sustainable management practices and increasing agricultural production. The microbial communities of plants correspond to different plant environments that play important roles in plant growth and soil health. Currently, a significant amount of information is available on microorganisms and their beneficial roles within plant systems. There is an immediate need to put microbial innovations into practice because of the remarkable functional potential of the plant microbiota to reduce biotic and abiotic stresses in crop production. Plant-associated microbiomes also provide physiological benefits for host plants, such as growth stimulation, nutrient cycling, stress tolerance, and disease resistance. In addition to promoting plant growth, phytomicrobiome members also assist in scavenging antioxidants by enhancing host resistance and reducing stress conditions that adversely affect plants. Therefore, it is crucial to understand phytomicrobiomes and their potential attributes for crop health management. In this review, recent progress in the relationship between the microbiome and plants at the plant-microbe, plant-plant, and microbe-microbe levels, as well as their deployment in achieving the aim of sustainable agriculture, has been discussed, along with potential areas for future research. Based on literature reviews, it revealed that microbiomes associated with plants provide several benefits at the development stage, including growth stimulation, nutrient supply, and biotic and abiotic resistance. Thus, the use of phytomicrobiomes can assist farmers in developing sustainable and profitable crop production to meet growing global demand, while also minimizing the impact on ecosystems and stakeholders.